2012
DOI: 10.1590/s0080-62342012000700003
|View full text |Cite
|
Sign up to set email alerts
|

Incapacidade relacionada à dor lombar crônica: prevalência e fatores associados

Abstract: A incapacidade relacionada à dor lombar crônica (DLC) é um fenômeno complexo e multifatorial. O objetivo desse estudo foi identificar a prevalência e os fatores associados à incapacidade em pacientes com dor lombar crônica. Estudo transversal com amostra composta por 177 pacientes com DLC, de três serviços de saúde; que responderam ao formulário com dados demográficos, ao Inventário de Depressão de Beck, às Escalas Oswestry Disability Index, de autoeficácia para dor crônica, Tampa de Cinesiofobia e de Fadiga d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
39

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 21 publications
4
44
1
39
Order By: Relevance
“…The results of self-reported pain in the present study are higher than those obtained by the aforementioned authors (6,(27)(28)(29)(30)(31). The Roland Morris disability findings were lower than those of other studies (28,30,31).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The results of self-reported pain in the present study are higher than those obtained by the aforementioned authors (6,(27)(28)(29)(30)(31). The Roland Morris disability findings were lower than those of other studies (28,30,31).…”
Section: Discussioncontrasting
confidence: 89%
“…The Roland Morris disability findings were lower than those of other studies (28,30,31). With respect to pain assessment, the mean results were similar to those reported by Stefane et al (31) and higher than those of Melo Filho et al (28).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have shown that LBP plays a major role in the activities of daily living, losses in work days, and productivity [2]. The incidence of chronic low back pain (CLBP) has been reported to be 9% to 21% in the general population and has been increasing steadily [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, people with low self-efficacy tend to drop out more easily when not succeed in a particular task, while people with high self-efficacy are more persistent to achieve their goals. Low self-efficacy causes the individual quitting daily activities, social and leisure activities [39].…”
Section: Interrelationship Among Quality Of Life Self-efficacy Adhementioning
confidence: 99%